SEKOLAH DASAR ISLAM (SDI) BERKARAKTER ‘FULL DAY SCHOOL’ DAN MADRASAH IBTIDAIYAH (MI) DI MATA MASYARAKAT - Salafudin (JURNAL PENELITIAN, 2010)
Islamic schools, including Madrasah Ibtida’iyah (Islamic Elementary Schools), have long been identified as traditional institutions with limited facilities, an excessive focus on Islamic studies, and less emphasis on science in their curriculum. As a result, their quality is often doubted and questioned, which is considered proportional to their low tuition fees and declining public interest. The emergence of Islamic schools labeled “Full Day School,” especially at the elementary level, has responded to these concerns. These schools seek to fulfill the expectations of students and parents for higher educational quality by providing better facilities and integrating Islamic studies with science in a comprehensive curriculum. This type of school is considered one of the best alternative options available. Using a descriptive approach, this qualitative research aims to describe Madrasah Ibtidaiyah (traditional Islamic elementary schools) and Full Day Islamic Elementary Schools (modern Islamic elementary schools) from the community’s perspective, as well as to explore their expectations regarding high-quality Islamic education. The data were collected purposively, and the research was conducted in Pekalongan City.